KERANGKA KONSEPTUAL KONSELING KELOMPOK BERBASIS ISLAM - Arina Rijki Aulia; Efa Findriani (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
Humans should not be separated from a problem, realized or not starting from among children, adolescents, adults and even the elderly can certainly have problems in life. Group counseling comes as an answer to the problems faced by every group, but seeing the situation and conditions of people who are less aware of the importance of counseling is a taboo thing, people think that konsleing is only used for people who have psychiatric problems. Indonesian society is also filled with a majority Muslim population. So we try to study Islamic-based group counseling as a solution for the wider community, especially Indonesia. This research method uses the library method, which is a method that studies various reference books and the results of similar previous studies that are useful for obtaining a theoretical basis for the problems to be studied.